Energy-Efficient Synthetic Method, X-Ray Diffraction Analysis and Thermal Decomposition of Cobalt (II) and Nickel (II) Schiff Base Complexes Derived from 2-Aminobenzothiazole - Sani, Salihu; Siraj, Ibrahim Tajo; Kurawa, Mukhtar Atiku; Koki, Isa Baba (ASEAN Journal of Science and Engineering, 2023)
A Schiff base was synthesized from the condensation reaction of 2-hydroxybenzaldehyde and 2-aminobenzothiazole via energy-efficient liquid-assisted mechanochemical synthesis (LAG). The Co (II) and Ni (II) complexes were also synthesized and characterized using IR, Solubility, TGA, PXRD, UV-Visible analysis, magnetic susceptibility measurement, conductivity measurement, and CHNS/O micro-analysis. In the IR analysis, the Schiff base spectrum revealed a prominent band at 1603 cm-1 (assigned to the azomethine v(C=N) stretching vibration), and the azomethine band shifted to 1621 and 1599 cm-1 in the Co (II) and Ni (II) complexes, respectively (indicating the formation of the expected complexes). In the TGA thermogram, Ni (II) and Cu (II) Schiff base complexes had decomposition temperatures of 184 and 181°C, respectively. The PXRD analysis revealed that the patterns of the ground mixture were different from the starting constituents, implying that the raw components were converted into the final product. The theoretical and experimental analytical data of C, H, and N for the Schiff base and complexes are in good agreement. The Schiff base ligand and its complexes were evaluated as agents for inhibiting the growth of pathogenic bacteria using the agar well diffusion method. According to antimicrobial activity studies, complexes exhibit stronger antibacterial activity than the Schiff base.